2018
DOI: 10.1002/ehf2.12366
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive levosimendan infusions for patients with advanced chronic heart failure in the vulnerable post‐discharge period

Abstract: Hospitalization for acute heart failure (HF) is associated with a substantial morbidity burden and with associated healthcare costs and an increased mortality risk. However, few if any major medical innovations have been witnessed in this area in recent times. Levosimendan is a first‐in‐class calcium sensitizer and potassium channel opener indicated for the management of acute HF. Experience in several clinical studies has indicated that administration of intravenous levosimendan in intermittent cycles may red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 35 publications
2
40
0
3
Order By: Relevance
“…LEAF studied short-term intravenous infusion of levosimendan, which appears to be more effective than placebo for treating patients with HF complicated by AMI [49]. The result of this confusion may be that the composite endpoint events are not uniform, and LAICA [50] and LeoDOR [51] are warranted to confirm those findings.…”
Section: Levosimendanmentioning
confidence: 99%
See 1 more Smart Citation
“…LEAF studied short-term intravenous infusion of levosimendan, which appears to be more effective than placebo for treating patients with HF complicated by AMI [49]. The result of this confusion may be that the composite endpoint events are not uniform, and LAICA [50] and LeoDOR [51] are warranted to confirm those findings.…”
Section: Levosimendanmentioning
confidence: 99%
“…Pharmacotherapy Tolvaptan TACTICS-HF [8], AQUAMARINE [9,10], Shirakabe et al [11], EVEREST [12], SECRET, QUEST, METEOR [13] Ivabradine SHIFT [14,15], INTENSIFY, ETHIC-AHF, Bagriy et al [17], CARVIVA HF [18] Sacubitril/valsartan PARADIGM-HF [19][20][21][22][23], PIONEER-HF [24,25], EVALUATE-HF [26], TRANSITION [27,28], PARAMOUNT [29,30], PARAGON-HF [31] Nebivolol SENIORS [33][34][35][36][37], Sessa et al [38], Brehm et al [39], ELANDD [40], CARNEBI [41] Levosimendan LIDO [42], SURVIVE [43], REVIVE [44], LevoRep [45], Zhang et al [46], LION-HEART [47], LEAF [48], Jia et al [49], LAICA [50], Leo-DOR [51] MRA Eplerenone: EPHESUS [75], EMPHASIS-HF [52][53][54][55]…”
Section: Treatments Key Trialsmentioning
confidence: 99%
“…In contrast, the LION-HEART study (n = 69) met its primary endpoint of NT-proBNP reduction, and it further showed a significant decline in the rate of all-cause death or HF hospitalization [54]. A meta-analysis of all available clinical trials, confirmed the effect of levosimendan on re-hospitalization in AdvHF [55]. The ongoing LeoDOR trial tests the hypothesis that repetitive levodimendan infusions will improve outcomes in AdvHF patients when applied during the vulnerable postdischarge period, when a significant proportion of readmissions occur [56].…”
Section: Inotropes In Advanced Heart Failurementioning
confidence: 98%
“…The need for a larger randomised study (or studies) in this area is being addressed by the Repetitive Levosimendan Infusion for Patients with Advanced Chronic Heart Failure trial (LEODOR; NCT03437226), a multicentre, randomised, double-blind, placebo-controlled, three-arm trial, which will examine the impact and safety of intermittent levosimendan therapy, started during the vulnerable phase after a recent hospitalisation for HF. [ 146 ] Treatment effectiveness will be assessed using a hierarchical composite clinical endpoint consisting of time to death or urgent heart transplantation or implantation of a ventricular assist device; time to non-fatal HF hospitalisation requiring IV vasoactive therapy; and time-averaged proportional change in NT-proBNP. Basing the trial on such an outcome measure should enhance the power to examine whether, compared with placebo, repeated use of levosimendan is associated with greater clinical stability over the course of subsequent weeks.…”
Section: Levosimendan In Current Usementioning
confidence: 99%